ANALISIS KEMAMPUAN MENYELESAIKAN SOAL MATEMATIKA MODEL PISA DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Muhammad Qusyairi; Tri Susilaningtyas; Fury Styo Siskawati (Jurnal Penalaran dan Riset Matematika, 2024)
This research aims to describe the ability to solve PISA model mathematics problems in terms of the adversity quotient. This type of research is descriptive with a qualitative approach. The subjects in this study were at least 1 camper subject, 1 quitter subject, and 1 climber subject. The data collection methods are documentation, questionnaires, tests, and interviews. The data analysis method is carried out in 5 stages: data transcription, data reduction, data validation or triangulation, data presentation, and conclusion. The research results obtained are (1) Students with low AQ (Quitter) have abilities up to level 2 in mathematical literacy in solving PISA model mathematics problems. (2) Students with medium AQ (Camper) have abilities up to level 4 in mathematical literacy in solving PISA model mathematics problems. (3) Students with high AQ (Climber) have the ability up to level 6 in mathematical literacy in solving PISA model mathematics problems.